An Interview with Peter Stanfield. The Who and the “White Heat” Generation: Politics, Influences and Modernity in the 1960s - Jordán Soriano, Ángeles (Complutense Journal of English Studies, 2023)
The 1960s is a decade that has frequently been re-assessed due to the vast number of socio-political changes which occurred in these years—many of them still affecting current society. In the UK these improvements were promoted under Harold Wilson’s administration (1964-1970), whose political agenda aimed to create an era of modernisation which soon permeated the British arts at all levels. In the particular case of the British band The Who, their songs deliver a particular testimony on issues such as modernity and commodity culture—in some cases, even anticipating a punk attitude, as Peter Stanfield, Emeritus Professor at the University of Kent, notes in one of his most recent books A Band with Built-In Hate: The Who from Pop Art to Punk (2021). The rising interest in this decade, the particularities of this band, and the recent release of material such as the present book have been the reasons to conduct this interview with Peter Stanfield. Moreover, the main aim of this dialogue is to shed light on the views on politics, modernity and society of a band who, due to its particular features—discussed in this interview—has a paramount role to be considered in British Cultural Studies.